ANALISIS YURIDIS DISPARITAS PUTUSAN PIDANA NARKOTIKA PADA JUDEX JURIST DAN JUDEX FACTIE (Studi Putusan Nomor 179/Pid.Sus/2020/PN.Trg., Nomor 207/Pid.Sus/2020/PNTrg dan 389/Pid.Sus/2021/PN Trg ) - Sunariyo, Sunariyo (LPPM, Universitas Muhammadiyah Riau, 2024)
Disparity in criminal decisions is the imposition of different criminal sanctions at each stage of legal action, both Judex Factie and Judex Jurist, so the aim of this research is to find out the judge's considerations in imposing a crime in each decision and to find out the causes of disparities in the decisions of Judex Factie judges and judges. Judex Jurist. This research method is juridical-normative with a statutory regulation approach and a case approach. The data collection technique is by analyzing laws and judge's decisions related to this research. The results of this research show that the judge's considerations in the Judex Factie decision were based on: a. Fulfillment of the elements of intentionally or without any legal right to offer for sale, selling, purchasing, receiving, being an intermediary in buying and selling, exchanging or handing over Category I Narcotics. In the Judex Juris judge's decision, it was based on the fulfillment of the more subsidiary elements of the indictment, namely each drug abuser and himself. And the cause of the disparity in the Judex Facti and Judex Juris decisions is caused by the judge himself because of the existence of freedom and independence of the judge as well as from the law itself, namely the absence of guidelines in sentencing so that the Judex Factie and Judex Jurist decisions are different, namely in Judex Jurist with a lighter decision